Santa Fe de Bogota. Real Audiencia records - Santa Fe de Bogota. Real Audiencia; Archivo General de Indias. Sección de Gobierno. Audiencia Santa Fe de Bogota
Selections from Archivo General de Indias, Gobierno, Audiencia Santa Fe de Bogota, legajos 117.
Photostats and transcripts of originals in the Archivo General de Indias (Seville).
Archivo General de Indias
Collection material in Spanish.
Keywords: Archives -- Spain; Colombia -- History -- 16th century; Spain -- Colonies -- America